Analysis Of Tradition & Modern In The Novels Of Manju Kapur - Dr. Eknath Tatte (Elementary Education Online, 2023)
This article aims to examine Manu Kapur's novels published so far, most notably Difficult Daughters (1998), Married Girl (2003), Home (2006), The Immigrant (2009), and Custody (2011) with a view to looking at culture and modernity in Manu Kapur's novels. This research paper is an effort to learn how Manju Kapur descibes the war between the traditional and modern life through her novels using her characters and how her novels observe the presence of privileged Indian women who challenge their simple rights to education, identity and life. All the characters of Manu Kapur's novels in particular, Virmati in Difficult Daughters, Astha in A Married girl, Nisha in domestic, Nina within Immigrant, and Shagun within Custody rebelled against tradition and tried to satisfy their desire for independence following modernity.